Understanding the Livelihood Implications of Reliable Honey Trade in the Miombo Woodlands in Zambia - Lowore, Janet (Frontiers in Forests and Global Change, 2020)
In some of Africa’s forests a natural endowment of floral resources and honey bee populations, have given rise to significant beekeeping activity. One such area is Mwinilunga, in the North-West Province of Zambia. The scale of this economic activity is influenced by the strength of beekeepers’ links to market. In recent decades, the demand for organic-certified bee products has created export potential and a private honey buying company started buying honey from Mwinilunga in 1996. By 2004 Forest Fruits Ltd had obtained organic certification and by 2016 the company was buying close to 1000 tonnes of honey a year, from 3000 registered beekeeper-suppliers. The importance of this growing honey trade for the local population has been recognised, but not explored in depth. A field study was carried out in two three-week periods in 2015 and 2016. The work involved focus group discussions with beekeepers and a questionnaire survey conducted with 165 beekeepers, and 64 non-beekeepers in four sites. The purpose was two-fold: to understand the livelihood implications of income from honey and to explore how the honey economy influences the relationship between beekeepers and forest. This paper reports on the results of the first question – livelihood implications. The results show that the reliability of the market and rising honey prices have increased the attractiveness of forest beekeeping. It was found that income earned is invested in education, in farming and as capital for other enterprises. Honey is often considered ‘the mother’ of other activities because no financial capital is required to generate this income. The low productivity of miombo woodland and soils do not offer a clear pathway out of poverty for the many millions of poor people who live in the miombo zone. This study demonstrates that where honey and beeswax trade is developed and dependable, forest beekeeping is becoming more attractive as an economic activity. Beekeepers are able to use the natural resources available, bees and tree nectar, to finance their varied and pressing livelihood needs in multiple ways.